Shaping ability of HyFlex EDM and ProTaper Gold files with or without using glide path files: An in vitro study - Maryam Gharechahi; Harir Ahmadi; Maryam Forghanirad; Melika Hoseinzadeh; Anahita Nouri (Saudi Endodontic Journal)
Introduction: The necessity of using a glide path before the canal preparation is inconclusive. Therefore, this study aimed to assess the shaping ability of two rotary systems in the maxillary first molars’ first mesiobuccal canal (MB1), with or without employing the glide path files. Materials and Methods: The MB1 canals of 100 extracted molars were randomly prepared using either HyFlex EDM (HEDM) or ProTaper Gold (PTG) systems (n = 50 each). Half of the samples in each group were prepared using ProGlider (PG) or HyFlex EDM Glide (HEG). The cone-beam computed tomography scanning was conducted before and after the instrumentation. The canal transportation, centering ability, and remaining dentin thickness were evaluated and compared between the groups using the independent sample t-test and Mann–Whitney U-test (α =0.05). Results: Using HEDM compared to PTG led to greater centering ability at the sub-furcation area (P < 0.05), lower canal transportation at 2 mm below furcation (P = 0.025), and more dentin removed at the middle area (P = 0.011). The systems’ centering ability and canal transportation were comparable when path files were used. Utilizing HEG with HEDM decreased dentin removal at 2 mm below furcation (P = 0.045) and middle area (P = 0.008). Canal preparation with HEDM-HEG caused less dentin removal at 2 mm below furcation than PTG-PG (P = 0.007). Conclusions: The HEDM system outperformed PTG regarding centering ability in the sub-furcation areas and canal transportation 2 mm below the furcation. However, HEDM showed more dentin removal in the middle region than PTG, which was resolved when HEG was used. Therefore, using PathFile with the HEDM system might be suggested.